The Role of Hybrid and Remote Work Models in Attracting Talent to Startups : A Focus on Local and International Recruitment - Sommer, Jakub; Orel, Marko, 1986-; Andera, Michal, 1984-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis explores how startups implement and leverage hybrid work models to attract and retain talent, as well as how they operate within these models in a way that benefits both the company and its employees. The research investigates whether flexibility through hybrid work serves as a strategic advantage in recruitment and retention efforts. It also examines how hybrid models are applied in practice, the challenges they pose, and their broader impact on employee satisfaction and startup scalability. To address these questions, the study draws on 13 semi-structured interviews with startup founders and senior professionals, primarily from Europe, with additional perspectives from one startup in the United States and one in Canada. The findings reveal that while hybrid work is widely seen as a standard expectation from candidates rather than a competitive advantage in terms of attractiveness within the startup environment, it plays a critical role in addressing key startups specific recruitment challenges. These include big uncertainty, limited talent for their niche solutions, cultural fit into the startups’ norms and financial constraints. Although only few startups explicitly promote hybrid work in their recruitment strategies due to its standardization, most recognize its importance in overcoming hiring challenges and improving work–life balance and employee retention. Additionally, the study also highlights major challenges associated with hybrid models, including productivity management, onboarding, perceived fairness, and maintaining company culture. However, many startups apply targeted mitigation strategies to address these issues. The conclusion emphasizes that, when implemented thoughtfully, hybrid work can serve as a foundational component of sustainable and scalable startup operations.
Vedoucí práce: Marko Orel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses